Epigenetic modulation of fungal pathogens: a focus on Magnaporthe oryzae - Aslam, Hafiz Muhammad Usman; Chikh-Ali, Mohamad; Zhou, Xin-Gen; Zhang, Shouan; Harris, Steven; Chanda, Ashok K.; Riaz, Hasan; Hameed, Akhtar; Aslam, Saba; Killiny, Nabil (Frontiers in Microbiology, 2024)
Epigenetics has emerged as a potent field of study for understanding the factors influencing the effectiveness of human disease treatments and for identifying alternations induced by pathogens in host plants. However, there has been a paucity of research on the epigenetic control of the proliferation and pathogenicity of fungal plant pathogens. Fungal plant pathogens such as Magnaporthe oryzae, a significant threat to global rice production, provide an important model for exploring how epigenetic mechanisms govern fungal proliferation and virulence. In M. oryzae, epigenetic alterations, such as DNA methylation, histone modification, and non-coding RNAs, regulate gene expression patterns that influence the pathogen's ability to infect its host. These modifications can enhance fungal adaptability, allowing the pathogen to survive in diverse environments and evade host immune responses. Our primary objective is to provide a comprehensive review of the existing epigenetic research on M. oryzae and shed light on how these changes influence the pathogen's lifecycle, its ability to invade host tissues, and the overall severity of the disease. We begin by examining the epigenetic alterations occurring in M. oryzae and their contributions to the virulence and proliferation of the fungus. To advance our understanding of epigenetic mechanisms in M. oryzae and similar plant diseases, we emphasize the need to address unanswered questions and explore future research directions. This information is crucial for developing new antifungal treatments that target epigenetic pathways, which could lead to improved disease management.